VARIATIONS OF NURSING DIAGNOSIS LANGUAGE IN STROKE PATIENTS BASED ON SDKI (STANDARD DIAGNOSIS NURSING INDONESIAN) - Ilkafah, Ilkafah; Qur'aini, Ouvin; Susanto, Joko; Pangestu Mei Tyas, Anestasia; Harisa, Akbar (Universitas Airlangga, 2024)
Introduction: The nursing system in Indonesia has an SDKI (Standard Diagnosis Nursing Indonesia) as the basis for determining nursing diagnoses. Inappropriate enforcement of nursing diagnoses based on the SDKI causes the objectives of the SDKI to not be fully achieved. Stroke is a state of cerebrovascular disease that can occur due to death in brain tissue caused by a lack of blood flow and oxygen flow to the brain. This study aims to find out the description of variations in writing nursing diagnoses in stroke patients based on the SDKI in Hospital RSUD Dr. Soegiri Lamongan. Methods: This research method is a documentation study, of 125 medical records of stroke patients at Hospital RSUD Dr. Soegiri Lamongan from August 2021 to February 2022, totaling 125 medical records. The data collection used consecutive sampling. The research was carried out in the working area of Hospital RSUD Dr. Soegiri Lamongan in March 2022. Results: The results showed that nursing diagnoses in patients with hemorrhagic stroke and non-hemorrhagic stroke were based on the SDKI Hospital RSUD Dr. Soegiri Lamongan, which are mostly written by nurses are impaired physical mobility (63%), variations in writing nursing diagnoses according to the SDKI (66%) and not according to the SDKI (34%), signs and symptoms in patients with hemorrhagic stroke and non-hemorrhagic stroke are mostly experienced weakness in moving the right extremity (31%). Conclusions: Nurses in establishing nursing diagnoses are appropriate based on the SDKI.